PERBANDINGAN KADAR SELULOSA DARI RUMPUT LAUT MERAH (RHODOPHYTA) - Alaydin, Syahrul; Bhernama, Bhayu Gita; Yulian, Muammar (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2020)
Seaweed was one of the marine resources. The cellulose potential of seaweed has no much research. Literature Review said summarized potential cellulose of red seaweed which analyzed. This review shows the greatest cellulose content was Gracilaria sp.